PARTISIPASI MASYARAKAT DALAM KEGIATAN KEBERSIHAN LINGKUNGAN DI KELURAHAN KAIRAGI WERU KECAMATAN TIKALA KOTA MANADO - Sangian, Novry (Universitas Sam Ratulangi, 2012)
Ethnic diversity in the city of Manado is one of the capital to build a structure of a society that leads to the development of a multicultural society. Diversity profession they pursue an idea that lives in the Kelurahan Kairagi Weru vary by profession, education level and social status. These conditions affect the understanding of environmental hygiene carried by each individual with colors taken from the culture of origin. Pockets of culture has had a major role to create a continuous process in order to create a clean state in the region. Cultural symbols become accessories in community participation on display in the halls of the complex to promote a healthy environment. The participation of the public in relation to environmental hygiene in the region reflects reinforced that each describes the diverse ethnic identities. It is very clear the people wanted to participate because of the things that cannot be abandoned. Willingness is also influenced by the presence of an opportunity or an invitation to participate and the public to see there are things that are useful in the activities undertaken Keyword : cultural, participation, healthy